2017
DOI: 10.3389/fncel.2017.00370
|View full text |Cite
|
Sign up to set email alerts
|

Central Projections of Antennal and Labial Palp Sensory Neurons in the Migratory Armyworm Mythimna separata

Abstract: The oriental armyworm, Mythimna separata (Walker), is a polyphagous, migratory pest relying on olfactory cues to find mates, locate nectar, and guide long-distance flight behavior. In the present study, a combination of neuroanatomical techniques were utilized on this species, including backfills, confocal microscopy, and three-dimensional reconstructions, to trace the central projections of sensory neurons from the antenna and the labial pit organ, respectively. As previously shown, the axons of the labial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
(122 reference statements)
1
5
0
Order By: Relevance
“…Distinct staining of sensilla located on the outer palp surface, as performed here, revealed that the projections originating from this site terminate in the two additional areas -the GNG and the ventral nerve cord. "Merging" the staining patterns obtained from the two labeling techniques utilized in the present study ( Figures 1B,C), forms a pattern that is very similar to that previously reported by several researchers using the classic mass staining technique ( Figure 1D; Kent et al, 1986;Lee and Altner, 1986;Zhao et al, 2013;Ma et al, 2017). This confirms the suggestion made by Kent et al (1986) that the axon projections to the LPOGs originated from sensory neurons housed inside the pit and that the branches seen in the GNG were parts of other sensory neuron types.…”
Section: Lpo Sensory Neurons Target the Antennal Lobes Exclusivelysupporting
confidence: 91%
See 3 more Smart Citations
“…Distinct staining of sensilla located on the outer palp surface, as performed here, revealed that the projections originating from this site terminate in the two additional areas -the GNG and the ventral nerve cord. "Merging" the staining patterns obtained from the two labeling techniques utilized in the present study ( Figures 1B,C), forms a pattern that is very similar to that previously reported by several researchers using the classic mass staining technique ( Figure 1D; Kent et al, 1986;Lee and Altner, 1986;Zhao et al, 2013;Ma et al, 2017). This confirms the suggestion made by Kent et al (1986) that the axon projections to the LPOGs originated from sensory neurons housed inside the pit and that the branches seen in the GNG were parts of other sensory neuron types.…”
Section: Lpo Sensory Neurons Target the Antennal Lobes Exclusivelysupporting
confidence: 91%
“…In all these studies, dye was applied to the truncated part of the peripheral labial-palp segment. Whereas the two last-mentioned reports insisted that all labeled axons were CO 2 -sensitive neurons projecting from the LPO (Zhao et al, 2013;Ma et al, 2017), the original paper suggested that the stained processes in the GNG arose from other sensory neurons on the labial palp (Kent et al, 1986). Thus, even though all previous studies have reported about LPO projections passing bilaterally to the LPOG in each antennal lobe, the total staining pattern including additional axon terminals in other central regions has been interpreted in various ways by the different investigations.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It receives axonal terminals originating mainly from the neurons of Böhm bristles and Johnston’s organ. Different sensory neurons project to distinct regions of the AMMC in many different insect species (Ma et al, 2017). In Drosophila , the AMMC is subdivided into five zones, while in the desert locust, it is subdivided into four regions (Kamikouchi et al, 2009; von Hadeln et al, 2018).…”
Section: Discussionmentioning
confidence: 99%